Diverse mechanisms drive fluoride enrichment in groundwater in two neighboring sites in northern China. (June 2018) - Li, Danni; Gao, Xubo; Wang, Yanxin; Luo, Wenting
Abstract: Excessive amounts of fluoride in drinking groundwater are harmful to human health, but the mechanisms responsible for fluoride enrichment in groundwater are not fully understood. Samples from two neighboring areas with endemic fluorosis were collected to test the hypothesis that there are distinctly different mechanisms responsible for the enrichment of fluoride in these groundwater. Hydrochemistry, stable isotopes and geochemical simulation were conducted together to investigate the fluoride spatial distribution and the diversity of responsible mechanisms. Our results showed that the spatial distributions of fluoride are different: I) high [F] in fresh shallow groundwater (SGQJ ) and II) medium [F] in fresh to brackish deep groundwater (DGQJ ) in the Qiji area; and III) medium [F] in brackish shallow groundwater (SGYH ) and IV) low [F] in fresh deep groundwater (DGYH ) in the Yanhu area. We also found that the fluoride concentration in groundwater is primarily controlled by the dissolution equilibrium of fluorite, as suggested by the correlation between [F] and [Ca]. However, there are other significant mechanisms: 1) for SGQJ, fluoride-bearing minerals (such as fluorite) dissolution, along with moderate evaporation, cation exchange and the more alkaline conditions are the driving factors; 2) for SGYH, the contributing factors are strong evaporation, the salt effect, dissolution of evaporites, gypsum and dolomite, bicarbonate-fluoride competition and anthropogenic activity; 3) for DGQJ, cation exchange, alkaline conditions and competitive adsorption are major factors; and 4) dolomite dissolution promotes the [F] increase in DGYH . Our findings suggest that the hydrogeochemical conditions play key roles in the enrichment of fluoride and that caution should be taken in the future when evaluating fluoride occurrence in groundwater, even in nearby areas. Graphical abstract: Image 1 Highlights: Groundwater samples were from two neighboring typical fluorosis areas. Significant difference of occurrences patterns of fluoride exist in aquifers in the two neighboring sties. Mechanisms diversity in controlling fluoride concentration were interpreted. Cautions should be taken when evaluating fluoride occurrence in groundwater, even in neighboring sites. Abstract : Significant differences in the spatial distributions of fluoride exist in the shallow and deep aquifers in two neighboring sites, and diverse mechanisms are responsible.